Political Institutions and Public Policy: The Co-Decision Procedure in the European Union and the Reform of the Common Agricultural Policy - Christophe Crombez; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
In this paper we study the implications of the introduction of the co-decision procedure for the European Union's Common Agricultural Policy and its refirm. We use a game-theoretical model of the legislative procedures in the European Union and show that the move from consultation to co-decision implies a shift of power from the Commission to the European Parliament. The implications for the Common Agricultural Policy depend on the configuration of preferences, the location of the status quo, and the bargaining powers in the Conciliation Committee. If the member states and the European Parliament are more opposed to refirm than is the Commission, the introduction of co-decision reduces the prospects for refirm of the European Union's Common Agricultural Policy.
Keywords: 330